2012
DOI: 10.3390/nu4060529
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Leucine and Pyridoxine-Containing Nutraceutical on Fat Oxidation, and Oxidative and Inflammatory Stress in Overweight and Obese Subjects

Abstract: Leucine stimulates tissue protein synthesis and may also attenuate adiposity by increasing fatty acid oxidation and mitochondrial biogenesis in muscle and adipocytes. Accordingly, the effects of a nutraceutical containing 2.25 g leucine and 30 mg pyridoxine (Vitamin B6) (NuFit active blend) were tested in cell culture and in a clinical trial. 3T3L1 adipocytes were treated with leucine (0.25 mM or 0.5 mM) and/or Pyridoxal Phosphate (PLP) (50 nM or 100 nM) for 48 h. For the clinical trial, twenty overweight or o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
72
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 37 publications
(50 reference statements)
3
72
1
Order By: Relevance
“…Criteria for a valid measurement was a minimum of 15 min of steady state, with steady state determined as less than 10% fluctuation in minute ventilation and oxygen consumption and less than 5% fluctuation in RQ. RQ was calculated as CO 2 production/O 2 consumption [16]. …”
Section: Methodsmentioning
confidence: 99%
“…Criteria for a valid measurement was a minimum of 15 min of steady state, with steady state determined as less than 10% fluctuation in minute ventilation and oxygen consumption and less than 5% fluctuation in RQ. RQ was calculated as CO 2 production/O 2 consumption [16]. …”
Section: Methodsmentioning
confidence: 99%
“…We have also recently shown leucine to interact synergistically with vitamin B6 to attenuate adiposity8 Pyridoxal phosphate inhibits adipocyte Ca 2+ influx in vitro,8 resulting in significant decreases in adipocyte fatty acid synthase expression and activity and corresponding reductions in adipocyte triglyceride content,8 because Ca 2+ signaling coordinately stimulates fatty acid synthase activity and inhibits lipolysis in adipocytes 913. Moreover, leucine and pyridoxal phosphate synergistically inhibit adipocyte triglyceride accumulation 8.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, leucine and pyridoxal phosphate synergistically inhibit adipocyte triglyceride accumulation 8. Consequently, the efficacy of a leucine (2.25 g/day)-B6 (30 mg pyridoxine/day) combination in stimulating fat oxidation in vivo was evaluated in a 28-day, placebo-controlled, randomized clinical trial with overweight and obese subjects and found to increase whole-body fat oxidation significantly by >30 g/day 8. However, this trial was of too short a duration to determine the efficacy of this combination in modulating body weight and composition.…”
Section: Introductionmentioning
confidence: 99%
“…Nutraceutical supplementation (leucine and pyridoxine), provides effective antioxidant and antiinflammatory influences, enhances fat oxidation and improves insulin signaling. 95,96 …”
mentioning
confidence: 99%